PENERAPAN METODE BLENDED LEARNING MODEL FLIPPED CLASSROOM UNTUK MENINGKATKAN HASIL BELAJAR SISWA/I KELAS VI PADA MATA PELAJARAN SKI MASA NEW NORMAL DI MI MUHAMMADIYAH SUNGAI PINANG KECAMATAN HULU KUANTAN KABUPATEN KUANTAN SINGINGI - Dandi Putra; Ikrima Mailani; Alhairi Alhairi (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2023)
The background of this research is the Covid-19 pandemic that hit the world in general and Indonesia in particular. This starts with the existence of policies/regulations from the government in education that cause new problems in the learning process in the classroom. This began with the government's option with Learning From Home (BDR) activities which made children dependent on the use of Smartphone technology. Then came the term New Normal which entered education with various rules that must be guided by educational institutions. So that in the learning transition during the Covid-19 to the New Normal, problems were found in the decline in student learning outcomes. This type of research is Classroom Action Research. Data collection uses interview, observation and documentation techniques, while the data analysis of test results uses quantitative and others are analyzed qualitatively descriptively by comparing student learning outcomes before the action with learning outcomes after the action. The results of this study can be seen at the time of the initial activity, namely Pre-Cycle, at the time of Pre-Cycle, the results of its application are seen with the number of learning outcomes 840 with an average of 64.62, 6 students who did not complete, 7 students who completed and the completeness 46.15%. Then after that the first cycle activity was carried out, namely the learning process using the Blended Learning Model Flipped Classroom method with the help of lectures in class, in this activity the application showed 910 learning outcomes with an average of 69.63, students who did not complete 5, students who completed there 8 and the completeness score is 61.54%. Although the first cycle has increased from the Pre-Cycle, it cannot be a measure of success because the success target has not been achieved. Then continued with cycle II, in this activity the implementation showed the number of learning outcomes 1110 with an average of 85.39, there were still 1 students who did not complete, 12 students who completed and the completeness score reached 92.31%. So it can be concluded that cognitive learning outcomes with measurement of learning outcomes test can be seen from the pre-cycle, cycle I and cycle II have increased and achieved the target of success.